Property and wealth in classical Sparta - Hodkinson, Stephen (The Classical Press of Wales, 2009)
The standard image of Sparta is of an egalitarian, military society which disdained material possessions. Yet property and wealth played a crucial role in her history. Classical Sparta's success rested on a compromise between rich and poor citizens. Economic differences were masked by a uniform lifestyle and a communal sharing of resources. Over time, however, increasing inequalities led to a plutocratic society and to the decline of Spartan power. Using an innovative combination of historical, archaeological, ands ociological methods, Stephen Hodkinson challenges traditional views of Spartan isolation from general Greek culture.